2021
DOI: 10.20960/nh.03649
|View full text |Cite
|
Sign up to set email alerts
|

Association between parental attitudes towards their offspring’s diet and children’s actual dietary habits — The SENDO project

Abstract: Association between parental attitudes towards their offspring's diet and children's actual dietary habits -The SENDO projectAsociación entre las actitudes de los padres hacia la dieta de sus hijos y los hábitos alimentarios reales de los niños: el proyecto SENDO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Lastly, although the questionnaires about parental knowledge of children's nutritional requirements and those about parental attitudes towards their child's dietary habits have not yet been validated, previous studies have shown that they are associated with diet quality in pediatric populations [39]. Our questionnaire on physical activity has not yet been validated either.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, although the questionnaires about parental knowledge of children's nutritional requirements and those about parental attitudes towards their child's dietary habits have not yet been validated, previous studies have shown that they are associated with diet quality in pediatric populations [39]. Our questionnaire on physical activity has not yet been validated either.…”
Section: Discussionmentioning
confidence: 99%
“…The participants' parents were categorized as having high (>70%), medium (40-70%), or low (<40%) nutritional knowledge. The parental attitudes and parental knowledge scores have been used in previous studies of the SENDO project [39].…”
Section: Assessment Of Covariatesmentioning
confidence: 99%